2009
DOI: 10.1002/pola.23326
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of nematic polyazomethine/single‐walled carbon nanotube composites prepared by in situ polymerization

Abstract: The synthesis and characterization of a series of nematic SWNT-polyazomethine composites are described. The composites were prepared by in situ polymerization in the presence of 1 wt % of chemically modified SWNTs in such a way that they were either dispersed or covalently bonded to the polymeric matrix. The presence of the SWNTs did not alter the thermal behavior of the polymer matrix and, therefore, highly oriented fibers could be melt-extruded from the composites at moderate temperatures, as revealed by str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…The applications of the polymer were huge in areas as they were used in medicine, transport, construction, aviation, and so on [1][2][3][4]. However, the preparation of PMMA generally involved the formation of unsaturated end groups and head-head (H-H) linkages due to the disproportionation and coupling reaction [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The applications of the polymer were huge in areas as they were used in medicine, transport, construction, aviation, and so on [1][2][3][4]. However, the preparation of PMMA generally involved the formation of unsaturated end groups and head-head (H-H) linkages due to the disproportionation and coupling reaction [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Few scientists investigated the influence of hydroxy functionalization and metal cross-linking on the fibre properties of LC polyazomethines [52][53][54][55]. Cerrada et al [52] synthesised LC polyazomethines with and without hydroxyl groups, as shown in Fig.…”
Section: Fibres and Nanocomposites With Lc Polyazomethinesmentioning
confidence: 99%
“…Although it generally impairs the properties of the nanotubes, at least for SWCNTs, the most common choice for realizing attractive CNT-liquid crystal polymer composites is the first one, to covalently functionalize the nanotubes. Either they are simply oxidized resulting in carboxylic acid groups attached to the CNT sidewalls [158,159] or one grafts more complex moieties to the nanotubes, specifically designed to enhance compatibility with the host [158][159][160]. Sahoo et al compared carboxylate group and hydroxyl benzoic acid (HBA)-functionalized MWCNTs for incorporation in a liquid crystalline polymer (the authors did not specify which phase the polymer formed) consisting of 80% HBA and 20% ethylene terphtalate (ET) [159].…”
Section: Carbon Nanotubes In Liquid Crystalline Polymers or Polymerizmentioning
confidence: 99%
“…In the study of Lafuente et al [158] three different functionalizations of singlewall CNTs were compared for integration into a nematic polyazomethine host. In addition to the standard carboxylate group attachment the authors prepared SWCNTs functionalized with CONH(CH 2 ) 6 NH 2 amines or with 2-methyl-1,4-phenylenediamines.…”
Section: Carbon Nanotubes In Liquid Crystalline Polymers or Polymerizmentioning
confidence: 99%